Variabilidade comportamental e seleção cultural: efeitos de esquemas análogos a reforçamento diferencial de variabilidade LAG e a CRF em processos de seleção de metacontingências - Kracker, Carolina Krauter (2013)
Metacontingencies are the product and the process of selection of cultural practices in the third level of selection by consequences, in which variation is a fundamental requisite for selection to occur. Three experiments were conducted with the objectives of investigate the effects of schemes analogous to differential reinforcement schemes of variability LAG, and CRF, upon the behavior variability in cultural selection processes, and to ascertain in which ways more or less variability along these processes would affect the selection of a new metacontingency, in the face of a change in the cultural consequences presentation criterion. In the Experiment I, 21 participants worked in trios, under the effect of schemes analogous to LAG 2 and LAG 1 for the products of responses of inserting numbers from 0 to 9 in spots placed in some computers´ screens. It was required, as a condition to the presentation of cultural consequences (bonus), that an aggregate product (PA) featured by an specific relation among the sums of the numbers inserted by the participants and by non-repetition of the sums between cycles, according to the n of the LAG contingence, was produced. It was observed that there wasn´t systematic production of this PA along more than two consecutive generations of participants and that only the specified relation among sums recurred along different generations. Stereotypies in the operant responses´ topographies and in the sums were found. In the face of the change in the criterion of presentation of the cultural consequences, featured by a different relation among the sums (new PA), the selection of/ by metacontingencies and cultural transmission occurred and the production of stereotypies was again observed. In the second experiment, that counted on 14 participants, similar experimental phases were conducted, except that there wasn´t a phase in which schemes analogous to LAG were in effect. The selection of/by metacontingencies and its transmission were verified in these conditions, and when the change in the criterion of presentation of the cultural consequences was made, a new cultural selection was observed in a similar moment of the occurrence of this phenomenon in the previous experiment; the practice was also transmitted. Behavior stereotypies were noticed, mainly in the first process of cultural selection that was described. There were 18 participants in the third experiment, in which a scheme analogous to LAG 1 for the sums was introduced; after 13 generations of participants the selection of/by metacontingencies was ascertained, as well as its transmission. It was observed that there was more variability in the responses topographies and in the sums, but patterns that indicated restrictions in the behavior variability were identified when the cultural selection occurred. It was concluded that the introduction of schemes analogous to LAG hampered the selection of/by metacontingencies and that a new cultural selection happened rapidly, despite of more or less behavioral variability in the microcultures´ stories previously the modification of the criterion related to the presentation of cultural consequences